1997
DOI: 10.1002/(sici)1096-9071(199704)51:4<332::aid-jmv12>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Impaired interferon induction of human MxA protein in chronic hepatitis B virus infection

Abstract: MxA protein is interferon inducible, and its role as an antiviral mediator is being studied in various viral diseases. Several cytokines, including type 1 interferons (alpha and beta), interleukins 2 and 12, and granulocyte, macrophage, and granulocyte-macrophage colony-stimulating factors, were tested for their ability to induce human MxA protein synthesis in peripheral blood mononuclear cells from 15 chronic hepatitis B virus-infected patients and 6 healthy subjects as controls. Constitutive MxA expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…In co-transfection experiments with the human MxA promoter and constructs expressing constitutively core (HBc) or precore (HBe) antigens, we have shown a clear inhibition of the reporter activity after IFN induction. This result was consistent in all cell lines tested, showing that the inhibition was not dependent on host cell factors and, thus, that it is not restricted to liver cells, which is in agreement with our previous observations in human mononuclear cells (Fernandez et al, 1997) and with the inhibition reported by others (Rosmorduc et al, 1999) in similar experiments made with defective HBV genomes. The major characteristic of this defective genome is the accumulation of the core protein in the cytoplasm of transfected cells and the authors concluded that this core protein might be involved in the reduced capacity to respond to IFN.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In co-transfection experiments with the human MxA promoter and constructs expressing constitutively core (HBc) or precore (HBe) antigens, we have shown a clear inhibition of the reporter activity after IFN induction. This result was consistent in all cell lines tested, showing that the inhibition was not dependent on host cell factors and, thus, that it is not restricted to liver cells, which is in agreement with our previous observations in human mononuclear cells (Fernandez et al, 1997) and with the inhibition reported by others (Rosmorduc et al, 1999) in similar experiments made with defective HBV genomes. The major characteristic of this defective genome is the accumulation of the core protein in the cytoplasm of transfected cells and the authors concluded that this core protein might be involved in the reduced capacity to respond to IFN.…”
Section: Discussionsupporting
confidence: 93%
“…We found no changes in the baseline levels of the signal transducers Jak1, Stat1 and Stat2 proteins or in the levels of Stat1 and Stat2 phosphorylation. These are the principal mediators associated with the cascade events produced upon binding of IFN-a/b to its receptor in the cytoplasm membrane (Pellegrini & Dusanter-Fourt, 1997), and the observation of unchanged levels of these proteins is in agreement with recent studies (Keskinen et al, 1999;Melen et al, 2000) and with our previous data in blood mononuclear cells isolated from HBV chronically infected patients (Fernandez et al, 1997). Cells from these patients showed a diminished capacity to express the MxA protein but not 29,59-oligoadenylate synthetase, another IFN-inducible gene, which suggests a specific effect over the MxA protein rather than a general interaction at a common signalling pathway.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations